Fungsi Pengawasan Partisipatif Dalam Mewujudkan Pemilu Demokratis - Bidja, Isnanto (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The involvement of the community in the political process is very necessary to be considered as the existence of political apathy in the general election. The political process can be said to be democratic when the community is the main actor in making political decisions, so that democracy guarantees the participation of the community itself. Participatory election supervision is a joint way of how the community can participate in supervising both campaigns, calm periods and election day by transforming moral strength into strength. with the consequence of having knowledge and skills about electoral and monitoring techniques. The main problem in this research is how to implement participatory supervision in realizing democratic elections?. The results show that participatory supervision plays a strategic role in the formation of responsive and impartial electoral law, implementation of election law by supervisors at the field level and the formation of a community legal culture/culture that can support the creation of participatory supervision for the realization of democratic elections in 2024.